Inflammation Associated Gene Expression in the Mammary Gland of Lactating Mothers Who Delivered Preterm and Were Randomly Assigned to a Standard vs Increased DHA Supplement. (7th June 2021) - Adams, Joselyn; Valentine, Christina; Rogers, Lynette; Karns, Rebekah; Murase, Masahiko; Fowler, Grace; Nommsen-Rivers, Laurie
Abstract: Objectives: Our objective was to characterize the mRNA-seq transcriptome of the mammary gland of lactating mothers who delivered preterm and were enrolled in a randomized control trial (RCT) of standard versus increased DHA supplementation. We hypothesized that inflammation associated gene expression would be attenuated in the increased DHA group versus the standard dose group. Methods: The RCT was completed by 8 participants randomized to standard of care DHA supplements (200 mg/day, STD group) and 10 randomized to increased DHA supplements (1000 mg/day, EXP group). High quality extracellular mammary epithelial cell mRNA was isolated from fresh milk fat and submitted to RNA-sequencing in n = 4 STD and n = 6 EXP DHA samples. Aligned and quantified reads were examined for differentially expressed genes using t-tests (DEG, p < 0.05 after false discovery rate adjustment). The resulting DEG list was intersected with the Broad Institute list of hallmark inflammation genes. Ontological analysis of DEGs was performed with Toppcluster. Results: There were 409 DEGs overall, including 9 hallmark inflammation genes. In the EXP group, up-regulation of inflammation-inhibiting genes included NFKBIA (FC = 4.0) and IL18BP (FC = 3.6); and down-regulation of pro-inflammatory genes included IL7R (FC = −3.6) and IL1RL1 (FC = −3.9). Ontological analysis revealed 5 clusters of up-regulated gene sets in the EXP group, including immune regulation and management of oxidative stress associated clusters. Strong up-regulation was also seen in the major milk proteins LALBA (3.8-fold increase) and CSN2 (3.4-fold increase). Conclusions: These findings reveal that increased DHA supplementation during lactation can modulate the expression of inflammation-associated genes within the mammary gland and support improved mammary gland function. These effects may have important clinical implications towards producing milk with a more optimal inflammasome profile and improving overall mammary gland health and function in lactating mothers who deliver preterm, with an overall benefit of reducing inflammation-driven morbidity in their premature infants. Future research with a larger RCT and greater interrogation of milk composition and volume is warranted. Funding Sources: NIH, Mead Johnson Nutrition.